Effect of Curcuma Domestica, Centella asiatica, Cera alba, Glycerin, Lemon Essence to Reduce Stretch Marks - Erinda Nur Pratiwi; Siti Nurjanah; Desy Widyastutik; Joko Santoso; Atiek Murharyati; Aris Prastyoningsih (Budapest International Research and Critics University, 2021)
Stretch marks or streaks occur in almost 90% of women. Stretch marks sometimes appear itchy in the scratch and around it. Not a few who complain about stretch marks. Although it cannot be completely eliminated, the condition can be minimized with early skin care Stretch marks. This study is a quantitative study with a quasi-experimental research design with a pretest-posttest with control group design, which was conducted on elementary school patients. In this research design, the grouping of the members of the experimental group and the control group is done by purposive sampling. Then pretest was carried out on both groups and treatment was given to the experimental group, then after some time a posttest was carried out on both groups. This research was conducted at the Faculty of Health, Kusuma Husada University, Surakarta, in young women with SD. Data collection method using observation sheets to measure the number of SD lines. The sample used was 14 people in the control group and 14 people in the intervention group. From the results of the study, it was found that the administration of Curcuma domestica ointment could reduce the number of Striae Distance (SD) lines in adolescent girls.